Different clinical factors associated with Staphylococcus aureus and Pseudomonas aeruginosa in chronic rhinosinusitis. Issue 8 (21st April 2015) - Zhang, Zi; Adappa, Nithin D.; Doghramji, Laurel J.; Chiu, Alexander G.; Cohen, Noam A.; Palmer, James N.
<x xml:space="preserve">Abstract</x> Background Staphylococcus aureus and Pseudomonas aeruginosa are common culture isolates in chronic rhinosinusitis (CRS). We aimed to determine whether they were associated with different clinical factors of CRS. Methods Adult CRS patients who underwent functional endoscopic sinus surgery (FESS) between October 1, 2007 and December 31, 2011 were recruited. Patient demographics, Lund‐Mackay computed tomography (CT) scores, 22‐item Sino‐Nasal Outcome Test (SNOT‐22) scores, disease characteristics, and medication use were collected prior to FESS. Intraoperative culture was obtained in a standard manner. We compared patients with isolates of S. aureus or P. aeruginosa to patients with other culture results and no bacterial growth, respectively. Multivariate logistic regression was performed. Results A total of 376 patients met criteria; 104 patients (28%) had S. aureus, 32 (9%) had P. aeruginosa, and 10 patients (3%) had no bacterial growth. After adjusting for all clinical factors, compared to patients with positive culture other than S. aureus, patients with S. aureus had 1.9 times increased odds of having nasal polyps (odds ratio [OR] = 1.9; 95% confidence interval [CI], 1.0 to 3.3; p = 0.036); when compared to patients with positive culture other than P. aeruginosa, patients with P. aeruginosa had 7.8 times increased odds of having prior FESS (OR = 7.8; 95% CI, 2.1 to 28.9; p = 0.002) (91% vs 58%; p < 0.001) and 3.6 times increased odds of having diabetes with marginal significance (OR = 3.6; 95% CI, 1.0 to 13.2; p = 0.053). The sample size in the no bacterial growth group was too small to draw firm conclusions. Conclusion S. aureus was more common in CRS patients with nasal polyps, whereas P. aeruginosa was more common in CRS patients with prior FESS history and possibly diabetes.